Rwanda Sends Envoy to IITA Nigeria on strategic agricultural collaboration - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In a move to deepen collaboration in agricultural research and innovation, the High Commissioner of Rwanda to Nigeria, Ambassador Christophe Bazivamo, visited the IITA headquarters in Ibadan recently. The visit marks a renewed commitment to building strategic partnerships between Rwanda and IITA in advancing agricultural transformation across Africa. Dr. Ehui reaffirmed IITA’s commitment to Rwanda and referenced ongoing initiatives in the country, including research and development in banana and cassava, the promotion of digital agricultural technologies, and the development of improved seed varieties. He proposed intensifying efforts to drive forward initiatives that support youth entrepreneurship and inclusive agricultural development.